The Role of Sustainability Disclosure in Shaping the Performance of State-Owned Enterprises: An Indonesian Perspective - Sanda Patrisia Komalasari; Khalilul Rahman; Andesta Brilian Nelson (Jurnal Eksplorasi Akuntansi, 2026)
Despite the growing emphasis on sustainable development, the extent to which sustainability transparency influences the performance of state-owned entities remains empirically debated. This study investigates the impact of sustainability disclosure on the corporate performance—conceptually defined as "financial health"—of Indonesian State-Owned Enterprises (SOEs). Utilizing a sample of 61 non-bank SOEs from 2018 to 2022, this research employs multiple linear regression with unbalanced panel data. Sustainability disclosure is measured comprehensively using 85 indicators from the GRI Standards, while corporate performance is assessed through the regulatory framework of Decree No. KEP-100/MBU/2002. The results demonstrate that sustainability disclosure does not have a significant effect on the performance of Indonesian SOEs. This lack of significance suggests that sustainability reporting in Indonesian SOEs may still be at a symbolic stage, primarily serving as a tool for legitimacy rather than a driver of substantive performance improvement. These findings imply a need for more stringent enforcement of sustainability regulations and a shift from quantitative reporting to qualitative integration of ESG practices to genuinely enhance SOE value.